Kreowanie wizerunku jednostek terytorialnych: Creating the image of territorial units - Chrząścik, Marcin (Management and Administration Journal, 2021)
The publication is on the needs and how to build the image of units. The issue of image more boldly penetrates the government within the meaning of individual and collective, and the local and regional level. Article is intended for practitioners, local government, local community organizations and students interested in this special issue of territorial marketing in terms of the application of the various groups of instruments promotion (advertising, public relations and sponsorship) to create the image units.